2005
DOI: 10.1385/cbb:42:1:013
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Cells Express Different Isoforms of the Calcium Channel α2/δ Subunit

Abstract: We examined developmental changes in calcium channel alpha2/delta subunit mRNA in skeletal muscle and their possible influence on L-type calcium currents (ICa-L). Several isoforms of alpha2/delta-1 mRNA were found in myotubes and muscle fibers, and their relative levels changed with time in culture or age of the animal. Levels of alpha2/delta-1a were largest in older myotubes and was the only alpha2/delta-1 isoform present in adult muscle. Both myotubes and muscle fibers also expressed low levels of alpha2/del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Thus, we examined Sk-sat differentiation starting from the day the media was changed to 2% serum (day 0) and followed their temporal gene expression up to day 6. It has been shown that Sk-sat calcium currents exhibit the greatest changes between day 2 to day 6 when placed in 2% serum, thereafter no significant changes were measured [15]. Therefore, we predicted that Sk-sat reached their differentiated stage when placed in 2% serum by culture day 6.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, we examined Sk-sat differentiation starting from the day the media was changed to 2% serum (day 0) and followed their temporal gene expression up to day 6. It has been shown that Sk-sat calcium currents exhibit the greatest changes between day 2 to day 6 when placed in 2% serum, thereafter no significant changes were measured [15]. Therefore, we predicted that Sk-sat reached their differentiated stage when placed in 2% serum by culture day 6.…”
Section: Resultsmentioning
confidence: 94%
“…Our previous experience with Sk-sat cultures [15], revealed that Sk-sat differentiation is accelerated when they are cultured in low serum media. For example, when serum concentrations are decreased from 20% to 2%, Sk-sat start forming myotubes by culture day 3, and show early spontaneous beating by day 4, with increasing beating frequency and myotube length by day 6 (Supplemental movie 2).…”
Section: Resultsmentioning
confidence: 99%
“…Generally, motor nerve signals activate SR network through ryanodine receptor signal, causes calcium release from SR Ca 2+ store, the cytosolic calcium elevation subsequently activates tropomyosin and troponin-1, induces F-actin formation and finally leads to contraction (Ogawa et al, 2002). On the other hand, recent reports (Lin et al, 2005;Nabhani et al, 2005) showed that skeletal muscle also possesses functional dihydropyridine-sensitive (L-type) calcium channel, which is genetically distinguished from L-type Ca 2+ channel on vascular smooth muscle, and mutation of a1 subunit (CACNA1S) in patients causes periodic paralysis (Jurkat-Rot et al, 1994;Kawamura et al, 2004), indicating that pathophysiological Ca 2+ influx also has an important role (B) Caspase-12 activation was inhibited at calcium-free condition. Cells were treated with agents for 30 min and allowed to postincubate with DM for 2 to 6 h. Then they were harvested and assessed for immnoblotting along with the method of Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle weakness could be an important side effect of L-CCB therapy as skeletal muscles also express an isoform of L-type channels. [9]…”
Section: Introductionmentioning
confidence: 99%